Multimerization of DAB-1 onto Au GNPs affords new potent and selective N-acetylgalactosamine-6-sulfatase (GALNS) inhibitors. Issue 44 (31st October 2018) - Matassini, C.; Vanni, C.; Goti, A.; Morrone, A.; Marradi, M.; Cardona, F.
Abstract : Gold glyconanoparticles (Au GNPs) decorated with the natural iminosugar DAB-1 at different densities are reported. Abstract : Gold glyconanoparticles (Au GNPs) decorated with the natural iminosugar DAB-1 at different densities are reported. These new multivalent iminosugar architectures strongly and selectively inhibit N -acetylgalactosamine-6-sulfatase (GALNS), whose deficiency is connected to the lysosomal storage disease Morquio A. The combination of the dendrimeric technique with the synthetic strategy employed for Au GNP preparation allowed the enhancement of the multivalent presentation of the iminosugar onto the surface of gold nanoparticles, which resulted in the best GALNS inhibitor reported to date (IC50 = 520 nM).